Evaluating the Impact of Problem-Based Learning on Critical Thinking Skills in Undergraduate Nursing Students - Liaqat, Ayesha; Shafi, Maria (Biological and Clinical Sciences Research Journal, 2025)
Critical thinking is an essential competency for nursing professionals, enabling them to make informed clinical decisions and ensure patient safety. In Pakistan, traditional lecture-based pedagogies dominate nursing education, often limiting the development of higher-order cognitive skills. Problem-based learning (PBL) has emerged as an effective student-centered strategy to enhance critical thinking, but its application in Pakistani nursing curricula remains limited. Objective: To evaluate the effectiveness of problem-based learning in improving critical thinking skills among undergraduate nursing students in a tertiary care teaching hospital in Pakistan. Methods: A quasi-experimental pre- and post-intervention study was conducted from April to September 2024 at the NMC Multan. A total of 86 undergraduate nursing students were recruited through non-probability convenience sampling. Participants underwent six weeks of structured PBL sessions integrated into their curriculum. Critical thinking skills were assessed before and after the intervention using a validated critical thinking disposition inventory. Data were analyzed using SPSS version 25, employing paired t-tests and ANOVA to determine statistical significance, with a p-value ≤ 0.05 considered significant. Results: Post-intervention analysis revealed significant improvements in all domains of critical thinking: interpretation (p = 0.000), analysis (p = 0.000), evaluation (p = 0.000), inference (p = 0.000), and explanation (p = 0.000). The overall mean critical thinking score increased from 15.6 ± 3.5 to 20.5 ± 2.9 (p < 0.001). Senior students (3rd and 4th year) demonstrated greater improvements compared to juniors (p = 0.034), while no significant gender-based differences were observed (p = 0.210). Conclusion: Problem-based learning significantly enhances critical thinking skills among undergraduate nursing students and should be integrated into nursing curricula in Pakistan to promote clinical competence and professional readiness.